SOIL CARBON AND NITROGEN STOCKS IN SCOTS PINE (Pinus sylvestris L.) AFFORESTATION AREAS OF THE ALPINE BELTS OF TURKEY - E. Çomaklı (Journal of Animal and Plant Sciences, 2023)
Forest ecosystems play an important role in reducing the negative effects of global climate change. The soil is considered a significant factor in carbon pools in forest ecosystems. Many studies have been carried out to evaluate carbon and nitrogen stocks in forest ecosystems, but the number of studies examining the change depending on altitude is limited. The study aims to determine the differences in soil organic carbon (SOC) and nitrogen (N) stocks in Scots pine (Pinus sylvestris L.) afforestation at different altitudes of the same age in Erzurum province, based on the assumption that SOC and N stocks may vary depending on altitude. In this regard, 22 soil samples were taken from each afforestation from soil depths at 0-10, 10-20, 20-30 by a random method to represent two afforestation. Sampling and evaluation of results were made considering the International Panel on Climatic Change (IPCC) guideline recommendations. Estimated results indicated that soil depth carbon stocks at 0-30 cm are 128.5 Mg C ha-1 at high altitude (P1) afforestation and 109.3 Mg C ha-1 at low altitude (P2) afforestation. Nitrogen stocks are 10.83 Mg ha-1 (P1) and 12.86 Mg ha-1 (P2), respectively. Altitude has affected C and N stocks. Hence, this effect should be included for research on stock levels (especially estimation equations). Considering the upper layer's soil organic carbon stock, particularly in silvicultural initiatives in afforestation areas, is critical. Furthermore, the amount of carbon and nitrogen stored in the soil should not be overlooked in greenhouse gas inventories, and ecology-specific management plans should be established in this sense.
Keywords: Scots pine; afforestation; soil organic carbon stock; nitrogen stock; stratification ratio